Noncoding RNA-encoded peptides in cancer: biological functions, posttranslational modifications and therapeutic potential - Shiming Tan; Wenjuan Yang; Zongyao Ren; Qiu Peng; Xuemeng Xu; Xianjie Jiang; Zhu Wu; Linda Oyang; Xia Luo; Jinguan Lin; Longzheng Xia; Mingjing Peng; et al. (Journal of Hematology & Oncology)
Abstract In the present era, noncoding RNAs (ncRNAs) have become a subject of considerable scientific interest, with peptides encoded by ncRNAs representing a particularly promising avenue of investigation. The identification of ncRNA-encoded peptides in human cancers is increasing. These peptides regulate cancer progression through multiple molecular mechanisms. Here, we delineate the patterns of diverse ncRNA-encoded peptides and provide a synopsis of the methodologies employed for the identification of ncRNAs that possess the capacity to encode these peptides. Furthermore, we discuss the impacts of ncRNA-encoded peptides on the biological behavior of cancer cells and the underlying molecular mechanisms. In conclusion, we describe the prospects of ncRNA-encoded peptides in cancer and the challenges that need to be overcome.